Aplikasi Penjualan Barang Toko Sembako Di Kawasan Pasar Induk Palembang Berbasis Android - raffiki; M. Soekarno Putra (Teknik Komputer Politeknik Negeri Sriwijaya, 2023)
Abstract The Main Market is a central market that sells a variety of daily necessities, its activities are the same as a regular market, except that in the main market most of the buyers are people who want to resell the goods that have been purchased, by buying with a large number of parties who can get it. cheap price for resale. System development method using web engineering. To implement this sales application, supporting components are needed in order to work properly. These components include using the JAVA programming language, PHP and data storage using the MySQL database. The design of this system is expected to help and overcome the problems that exist in the Main Market so that it can be useful for interested parties. The purpose of this research is to create an application that can make it easier to sell the goods on offer, and make it easier to make online sales transactions so that they can be done anytime and safely with a wide market area coverage through digital markets, and can increase sales. Keywords— application, sales, web engineering, android